2018
DOI: 10.3390/jmse6030075
|View full text |Cite
|
Sign up to set email alerts
|

Free Surface Characteristics of Flow around Two Side-by-Side Circular Cylinders

Abstract: The three-dimensional free surface characteristics of flow around two equal diameter cylinders in a side-by-side arrangement were studied numerically. The flow fields were simulated with a three-dimensional finite volume method based on the RNG k-ε model for Reynolds number Re = 1.0 × 10 4. The volume-of-fluid method was applied to track air-water interfaces. Computations were performed for gap ratios of 1.25, 1.5, and 1.75 to examine the influence of the gap between two cylinders, and for distance to diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A zero value of F corresponds to a cell with no fluid, and a unit value indicates that the cell is full of water. A cell with an F value of between zero and one must contain a portion of the free surface [23,24]. The isosurface of F = 0.55 is defined as the free surface location.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…A zero value of F corresponds to a cell with no fluid, and a unit value indicates that the cell is full of water. A cell with an F value of between zero and one must contain a portion of the free surface [23,24]. The isosurface of F = 0.55 is defined as the free surface location.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Re D = 6000 Re D = 10, 000 for Re D = 10,000 at T/D between 1.5 and 1.75 [34], about which T/D = 1.7 in the present case falls within), the present numerical model overestimated their values in comparison to the experimental results in [37]. However, this difference in C d and C l with experimental results can be seen in all previous numerical studies reported in Table 4.…”
Section: T/dmentioning
confidence: 99%
“…A pair of vortexes in the wake of the two cylinders was observed, similar to the flow behind a cylinder. A similar flow is included in the work [19].…”
Section: Numerical Modelmentioning
confidence: 99%